2010
DOI: 10.4065/mcp.2009.0314
|View full text |Cite
|
Sign up to set email alerts
|

Use of Drug-Eluting Stents in Patients With Coronary Artery Disease and Renal Insufficiency

Abstract: Renal insufficiency (RI) has been shown to be associated with increased major adverse cardiovascular events after percutaneous coronary intervention. We reviewed the impact of RI on the pathogenesis of coronary artery disease and outcomes after percutaneous coronary intervention in the form of drug-eluting stent (DES) implantation in these high-risk patients. We searched the English-language literature indexed in MEDLINE, Scopus, and EBS-CO Host research databases from 1990 through January 2009, using as searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Consequently, the most important factor to predict TLR was the presence of HD, but not DM or usage of insulin. Stent restenosis in HD patients is still a major issue (12). Our study results indicated that they still had a higher restenosis rate even when using PES.…”
Section: Des In High-risk Patientsmentioning
confidence: 53%
See 1 more Smart Citation
“…Consequently, the most important factor to predict TLR was the presence of HD, but not DM or usage of insulin. Stent restenosis in HD patients is still a major issue (12). Our study results indicated that they still had a higher restenosis rate even when using PES.…”
Section: Des In High-risk Patientsmentioning
confidence: 53%
“…Therefore, technical factors such as poor dilation of the vessels were not the causes of the high TLR rate in HD patients. The incidence of restenosis in HD patients is high and stent restenosis is still a major issue (12). The reason for this might be that the mechanism of restenosis in HD patients is highly related to vessel shrinkage and neointimal hyperplasia (22).…”
Section: Hemodialysis Patientsmentioning
confidence: 99%
“…Chronic kidney disease (CKD): CKD has been recognized as a risk factor for coronary artery disease, 10) restenosis (in hemodialysis patients), 11,12) adverse clinical outcomes after both BMS and DES implantation, 13) and procedural failure. [14][15][16] It is also well known that there is a strong relationship between calcifi cation of plaque and renal function. [5][6][7] In this study, we report another new fi nding related to CKD, including those with end-stage renal disease on dialysis replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…31 However, among patients with CKD, in general, DES is deemed safer than BMS and associated with improved survival, [32][33][34][35] although not all studies are concordant in this regard. 36 In a large cohort of 121,446 patients with CKD, Tsai et al 37 reported that, at all stages of CKD, DES was associated with improved survival compared with BMS.…”
Section: Des Versus Bms: Mortality and In-stent Restenosismentioning
confidence: 99%